Shape Memory Alloys for Self-Centering Seismic Applications: A Review on Recent Advancements - Girolamo Costanza; Samuel Mercuri; Ilaria Porroni; Maria Elisa Tata (Machines)
Shape memory alloys (SMAs) have emerged as promising materials for self-centering seismic applications due to their unique properties of superelasticity and shape memory effect. This review article examines recent advancements in the use of SMAs for self-centering seismic devices, focusing on their mechanical properties, damping characteristics and applications in structural engineering. The fundamental principles of SMAs are discussed, including their phase transformations and hysteretic behavior, and their performance under various loading conditions is analyzed. The article also explores different SMA-based damping systems, with a particular emphasis on innovative self-centering friction dampers. Furthermore, the influence of factors such as alloy composition, heat treatment and loading parameters on the seismic performance of SMA devices is investigated. The review concludes by highlighting the potential of SMAs in improving the seismic resilience of structures and identifying future research directions in this field.